Preparation and investigation of structural, magnetic, and microwave absorption properties of aluminum‐doped strontium ferrite/MWCNT/polyaniline nanocomposite at KU‐band frequency. Issue 30 (31st March 2017) - Peymanfar, Reza; Javidan, Abdollah; Javanshir, Shahrzad
ABSTRACT: Aluminum‐doped strontium hexaferrite nanoparticle SrAl1.3 Fe10.7 O19 was prepared by sol–gel method and polyaniline (PANi) multiphase magnetic nanocomposite SrAl1.3 Fe10.7 O19 /MWCNT/PANi was synthesized through a sonochemical method by in situ polymerization. The morphology, structure, and magnetic properties of the nanocomposites are investigated by field emission scanning electron microscopy, X‐ray powder diffraction, Fourier transform infrared spectroscopy, and vibrating sample magnetometer. The electromagnetic interference shielding efficiency was evaluated in the KU‐band (12.4–18 GHz). The reflection loss (RL) value showed that the composites have an excellent absorbing property in the KU‐band, minimum −24.93 dB at 16.40 GHz with a bandwidth of 2.81 GHz (shielding effectiveness up to 10 dB) at a matching thickness 6.5 mm. The RL value of the SrAl1.3 Fe10.7 O19 /MWCNT nanocomposite was −15.92 dB at 15.84 GHz with a bandwidth of 1.66 GHz (with a shielding effectiveness up to 10 dB). These results disclose the remarkable microwave shielding ability of SrAl1.3 Fe10.7 O19 /MWCNT/PANi in KU‐band due to the interactive effect of the three components. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45135. Abstract :